IMPLEMENTATION OF THE VILLAGE FUND ALLOCATION (ADK) PROGRAM POLICY IN MUARA LAWA DISTRICT, WEST KUTAI REGENCY - Theodorus Amarilla Suryadinatha; Dandan Haryono; Irwan Waris (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
This study aims to analyze the implementation of the Village Fund Allocation Program (ADK) policy in Muara Lawa District, West Kutai Regency, with a focus on supporting and inhibiting factors. The study used a descriptive qualitative approach with key informants consisting of village heads, village officials, community leaders, and Muara Lawa District officials. The analysis was conducted by referring to the policy implementation theory of Mazmanian and Sabatier which emphasizes three main indicators, namely the characteristics of the problem (tractability of the problem), the ability of the policy to structure the implementation process (ability of statute to structure implementation), and non-policy variables that influence the implementation process (non-statutory variables). The results show that the implementation of ADK in Muara Lawa faces problems of limited human resource capacity, geographical constraints, and weak coordination between actors, even though regulations have provided a clear legal framework. On the other hand, local government support and community participation are important factors supporting program implementation. This study concludes that the effectiveness of ADK implementation requires strengthening the capacity of apparatus, optimizing coordination mechanisms, and increasing community involvement so that the policy truly provides tangible benefits for village development.